Abdullah Saeed's Progressive Ijtihad in the Application of Rechtsvinding Judges in Religious Courts - Abdul Hamid (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2022)
Every court judge has their perspective in deciding a case. A judge always strives to make legal discoveries as a form of justice and legal certainty. However, legal discovery efforts are not always uniform. Therefore, it is necessary to reconstruct the methodology for making legal discoveries. Through Abdullah Saeed's contextual approach with progressive ijtihad packaging to connect the disconnection of the spirit and soul of divinity, so that justice based on the almighty God, conscience, and common sense as the pinnacle of law can be felt by justice seekers. This research is library research using various literature sources as research data sources. The research findings of legal discovery by judges are only needed in inconcreto cases. Judges still stand on the general legal approach in reading Islamic law. The need to raise living laws to positive laws whose level of applicability is binding is to use rechtsvinding / legal discovery in the Religious Court. Thus by taking into consideration: First, homogenize the understanding of judges in finding a law, Second, the methodology of Islamic law and override the general methodology in reading unwritten law, as well as written law with the spirit of the Islamic spirit sholihun likulli zaman.